Particle transport simulations based on selfconsistency of pressure profiles in tokamaks - Danilov, A.V.; Dnestrovskij, Yu. N.; Andreev, V.F.; Cherkasov, S.V.; Dnestrovskij, A.Yu.; Lysenko, S.E.; Vershkov, V.A. (Вопросы атомной науки и техники, 2006)
Simulation of particle and heat transport was performed with the ASTRA code. The equations for the electron temperature and density, ion temperature and current diffusion were solved. For the heat transport we used the canonical profiles model. Three T-10 pulses with toroidal magnetic field 2.5 T, plasma current 250…255 kA, initial average density 1.3, 2.4 and 3.2×10¹⁹ m⁻³ respectively, on-axis 900 kW ECRH and D₂ puffing were considered. The model proved to describe rather fast penetration of the density disturbance from the edge to the core during 15…20 ms after gas puffing. The simulation of the density profiles agrees with experiment in Ohmic and ECRH phases, and during the gas puffing, describing the particle pump-out after ECRH switch-on. The neutral influx at the plasma edge increases after ECRH switch-on in agreement with Da measurements. Both the effective diffusion coefficient and pinch velocity decrease slightly when the plasma density is increased. A set of two Ohmic and three NBI MAST pulses were considered for comparison.